(untitled) (International Journal of Architecture and Urbanism, 2022)
Tourism is one of the sectors that Indonesia relies on increasing state revenues. One of the tourist destinations that is still being developed is Lake Toba. This region has the potential to grow and compete to become world-class tourism. But in the process of development, there are still some obstacles. One of the obstacles is information services and promotion about tourism in the Lake Toba area that is still not maximized. Researchers identified the need for a facility that can accommodate promotional activities and tourism information through the design of the Tourism Information Center in the Lake Toba area, precisely in Ambarita Village, Samosir. Analysis and concept of design using an interpretation approach to Neo Vernacular Architecture. The result of this study is a design from the Lake Toba Tourism Information Center.